PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNA SISTEM E-LEARNING - Suharno Pawirosumarto (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. The study aims at analyzing and explain the influence of system quality,information quality, service quality to user satisfaction e-learning system in the Masterof Management UMB. Total population of this study were 451 students with a totalsample of 82. The sampling technique using proportional random sampling. Theanalytical method used GSCA (Generalized Structured Component Analysis). Theresults showed that the system quality, information quality, and service qualitysignificantly influence user satisfaction e-learning system. The better the perception ofthe quality system, the quality of information, and the quality of service it will furtherincrease user satisfaction.